Map? or List?based Recommender Agents? Does the Map Metaphor Fulfill its Promise? - Reitsma,Reindert; Hsieh,Ping-Hung; Diekema,Anne; Robson,Robby; Zarsky,Malinda (Information Visualization, 2016)
We present a spatialization of digital library content based on item similarity and an experiment which compares the performance of this spatialization relative to a simple list-based display. Items in the library are K-12 science and engineering learning resources. Spatialization and visualization are accomplished through 2D interactive Sammon mapping of pairwise item similarity scores based on the joint occurrence of word bigrams. The 65 science teachers participating in the experiment were asked to search the library for curricular items they would consider using in conducting one or more teaching assignments. Results indicate that whereas the spatializations adequately capture the salient features of the library’s content and teachers actively use them, item retrieval rates, task-completion time and perceived utility do not significantly differ from the semantically poorer but easier to comprehend and navigate list-based representations. These results put into question the usefulness of the rapidly increasing supply of information spatializations.
Keywords: BIS; Supply Chain